2022
DOI: 10.30621/jbachs.1004095
|View full text |Cite
|
Sign up to set email alerts
|

The Identification of the Relationship Between Oncology Patients’ Care Dependency and Anxiety Levels

Abstract: Introduction: This study aims to identify the relationship between oncology patients' care dependency and anxiety levels. Material and Methods:The research data were collected by using the individual Identification Form, the Care Dependency Scale, and the Beck Anxiety Inventory via the interviews held with 142 cancer patients hospitalized at the oncology clinic. The independent samples t-test, one-way analysis of variance, and the Pearson correlation test were used in the analysis of research data. Results: In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…24,25 Bilgin et al reported that the CDS score of inpatients in the oncology clinic was 60.1±17.34, and 37.83±21.42 in another study. 18,26 In the study of Koyuncu, the CDS score was similar in patients who received chemotherapy treatment (68.98±15.89). 27 In general, it can be said that care dependence in patients in the radiation oncology clinic is at a moderate level.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…24,25 Bilgin et al reported that the CDS score of inpatients in the oncology clinic was 60.1±17.34, and 37.83±21.42 in another study. 18,26 In the study of Koyuncu, the CDS score was similar in patients who received chemotherapy treatment (68.98±15.89). 27 In general, it can be said that care dependence in patients in the radiation oncology clinic is at a moderate level.…”
Section: Discussionmentioning
confidence: 92%
“…25 Prolongation of hospitalized patients increases care dependency of patients. 25,26,29 Being older supports this situation. 25,30 In the study of Bilgin et al, it was stated that 60.2% of the group aged >65 years were care dependent.…”
Section: Discussionmentioning
confidence: 93%